Understanding the Healing Potential of Ibogaine through a Comparative and Interpretive Phenomenology of the Visionary Experience. (4th March 2018) - Rodger, James
Abstract: Ibogaine is a hallucinogenic alkaloid, derived from Tabernanthe iboga, a plant unique to the rainforests of West Africa. Its traditional use as an epiphanic sacrament in local magico‐religious practice inspired its appropriation by Western drug addicts by whom it is now hailed as both a catalyst of psychospiritual insight and an effective alleviator of cravings and withdrawal. While scientific and early clinical studies confirm its role in reducing physical withdrawal and craving, debate continues concerning the significance of its "visionary" properties. An analysis of many addicts' testimonies of recovery, however, places the visionary experience at center stage. I set out to understand mechanisms of transformation and healing, via a comparative phenomenological exploration of this experience, through the opposing lenses of psychoanalysis and cultural constructivism. I propose that at the heart of the healing encounter is a culturally shaped creative journey to an imaginal unspoilt state in personal or collective history. How this experience is recovered and integrated into life is critically considered. I argue a secular account is vital as the ibogaine scene strives toward social and medical legitimacy. If and how such a framework can sit alongside spontaneously emergent spiritual and religious idioms and experience will also be tentatively explored.